Rate of decline of fetal base excess after neuraxial anesthesia for scheduled cesarean deliveryAJOG Global Reports at a Glance - Alessandro Ghidini, MD; Kelly Vanasche, BSN; Anna Locatelli, MD (Elsevier, 2023)
BACKGROUND: In scheduled cesarean deliveries, the rate of decrease in the umbilical artery pH is related to the severity of maternal hypotension and the interval from spinal placement to delivery. Base excess values have greater use than umbilical artery pH values to time the duration of fetal acidemia because they demonstrate a linear rather than logarithmic correlation with the degree of acidosis. OBJECTIVE: This study aimed to evaluate the rate of decline in the fetal base excess in scheduled cesarean deliveries that were converted to emergency cesarean delivery owing to fetal bradycardia following spinal anesthesia STUDY DESIGN: All cases of scheduled cesarean deliveries in gestations at >34 weeks' gestation under spinal anesthesia that were converted to emergency cesarean deliveries owing to fetal bradycardia in the period May 2019 to May 2021 were reviewed. Included were those with (1) a preoperative reactive nonstress test and (2) fetal acidemia (umbilical artery pH <7.20). Excluded were those with anesthesia other than spinal and a birthweight below the 10th percentile for gestational age. Time intervals between the completion of spinal anesthesia and delivery were calculated and related to umbilical cord gas analytes. RESULTS: From a cohort of 1064 scheduled cesarean deliveries, 7 fulfilled the study criteria yielding 8 neonates. Mean ± standard error of the mean interval of spinal anesthesia to delivery was 15.0±1.9 minutes, and the decrease in mean blood pressure after spinal anesthesia was 39.1±3.0 mm Hg. Umbilical artery base excess ranged from −5.2 to −16.6 mmol/L (median, −8.0). Based on published normative data of prelabor fetal umbilical artery base excess (−2±0.6 mmol/L), the mean rate of base excess decrease was 0.38±0.25 mmol/minute. CONCLUSION: The rate of decrease in base excess when scheduled cesarean deliveries are converted to emergency cesarean deliveries owing to fetal bradycardia related to spinal anesthesia (1 mmol/2.6 min) matches the estimated rate of loss of base excess (1 mmol/2-3 minutes) reported in cases of severe bradycardia or sentinel events during labor.